EVALUASI IMPLEMENTASI PENILAIAN PEMBELAJARAN KELOMPOK PRODUKTIF DI SMK NEGERI 1 WATANSOPPENG - Motondu, Nemiati; Rusyadi, Rusyadi (Universitas Negeri Makassar, 2017)
The study aims at describing the implementation of evaluation on productive group learning in SMKN 1 Watansoppeng based on antecedents component, transaction, and output. This study is the kind of evaluasi research using contenance stake model, which consists of antecedents, transaction, and output. The subjects of the study were teacher of productive learning group, class II students in fashion program at SMKN 1 Watansoppeng in Lalabata subdistrict of Soppeng district and industrial parties. Data was collected by conducting interview and documentation. Data was analyzed by employing descriptive qualitative and quantitative analysis. The results of the research shows that (a) the implementation of evaluation on productive group learning in SMKN 1 Watansoppeng based on antecedents component has been well planned, (b) the implementation of evaluation of productive groupÂ learning in SMKN 1 Watansoppeng based on transaction component has been well planned, (c) the output component of productive learning in SMKN 1 Watansoppeng shows good result.